2022
DOI: 10.3390/foods11081111
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Cymbopogon citratus D.C. Stapf Essential Oil with Spray Drying: Development, Characterization, and Antioxidant and Antibacterial Activities

Abstract: This study aimed to microencapsulate Cymbopogon citratus essential oil (CCEO) with spray drying using maltodextrin and gelatin. The effects of the operational conditions (inlet temperature (130–160 °C), CCEO concentration (5–15%), maltodextrin concentration (10–20%)) on the physicochemical stability and antioxidant and antibacterial activities of the CCEO microcapsules were determined. The CCEO microencapsulation process had yield and encapsulation efficiency values varying from 31.02 to 77.53% and 15.86–61.95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The microencapsulation efficiency was determined according to [ 22 ]. This measurement indicates the essential oil’s ability to be retained by the encapsulating matrix and was determined based on the oil content and the oil content retained after the drying process.…”
Section: Methodsmentioning
confidence: 99%
“…The microencapsulation efficiency was determined according to [ 22 ]. This measurement indicates the essential oil’s ability to be retained by the encapsulating matrix and was determined based on the oil content and the oil content retained after the drying process.…”
Section: Methodsmentioning
confidence: 99%
“…110 EO of cymbopogon citratus was encapsulated with different combinations of gelatin and MD at 130, 145 and 160°C, and the microencapsulates showed lower moisture content when spray drying was done at 160°C. 111,112 A kenaf seed oil spray dried with protein base (Sodium caseinate: β-cyclodextrin) at 1:4, with carbohydrate base (gum arabic:β-cyclodextrin) at 1:4 and mixed base (gum arabic:sodium caseinate:β-cyclodextrin) at 1:4, showed higher moisture content in carbohydrate base. The encapsulation efficiency was highest in the carbohydrate mix.…”
Section: Effect Of Inlet-outlet Temperaturementioning
confidence: 99%
“…it was observed that an increase in inlet temperature leads to an increase in moisture and surface oil content with deformed microcapsules of pumpkin seed oil in maltodextrin: whey protein:guar gum (15.40:3.90:0.50) at 130 and 180°C 110 . EO of cymbopogon citratus was encapsulated with different combinations of gelatin and MD at 130, 145 and 160°C, and the microencapsulates showed lower moisture content when spray drying was done at 160°C 111,112 . A kenaf seed oil spray dried with protein base (Sodium caseinate: β‐cyclodextrin) at 1:4, with carbohydrate base (gum arabic:β‐cyclodextrin) at 1:4 and mixed base (gum arabic:sodium caseinate:β‐cyclodextrin) at 1:4, showed higher moisture content in carbohydrate base.…”
Section: Factors Affecting Spray Dried Productsmentioning
confidence: 99%
“…Anxiolytic, anticonvulsant, and maybe preventative qualities against Alzheimer’s disease are among the plant’s neuroprotective benefits that are linked to volatile components including citral, geraniol, and linalool [ 13 , 14 ]. As evidenced by its topical use in lowering skin erythema and edema [ 15 ] and its inclusion into chitosan bioactive films for skincare applications [ 16 ], lemongrass also has antioxidant [ 9 , 17 , 18 ] and anti-inflammatory effects. The biological activities of C. citratus have been attributed to the secondary metabolites present in both the plant matrix and essential oils.…”
Section: Introductionmentioning
confidence: 99%